Pengadaan Sarana dan Prasarana Pendidikan dalam Menunjang Mutu Pembelajaran di SDN Lubuk Tua Kabupaten Musi Rawas - Irwan Fathurrochman; Siswanto Siswanto; Revi Anggraeni; K. Sathish Kumar (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2021)
The purpose of the provision of facilities and infrastructure is to meet the needs of equipment or equipment that can support the learning process in order to create an effective and efficient learning process. The approach used in this research is a qualitative descriptive approach. With the data method carried out by observation, interviews and documentation. Source of data, primary data is data sourced from school principals and managers of facilities and infrastructure at SDN Lubuk Tua. Secondary data is data obtained from other parties and documents related to data. Qualitative data were analyzed through data reduction, data retrieval, and withdrawal (verification). Procurement planning activities are carried out by holding meetings together to get information from teachers about what is needed in the learning process activities. The procurement of facilities and infrastructure is carried out by submitting a Budget Plan (RAB) by teachers and then approved by the head. The provision of facilities and infrastructure can support the quality of learning because school facilities and infrastructure are adequate, the learning process will run well and an effective and efficient learning process will be created